The French two-stage vertical flow constructed wetland in subarctic climate - Klapp, Rasmus; Hedström, Annelie; Molle, P.; Herrmann, Inga (Luleå tekniska universitet, Arkitektur och vatten, 2022)
Conventional small wastewater treatment plants in Sweden produce a sludge that needs to be collected and transported long distances to a centralised treatment facility. As many of these small plants are old and need replacement, the question arises weather a more sustainable solution is possible. The French two-stage vertical flow constructed wetland (VFCW) is a method where very little sludge handling is required, as the sludge is treated on-site. Therefore, this study aims to investigate cold climate performance of such a system in northern Sweden. A pilot-scale VFCW was built and sampled for BOD, nutrients and microplastics since November 2021. Results indicate that treatment performance is adequate and that microplastic can also be treated. ISBN för värdpublikation: 978-2-9585706-0-6